Application of a Holed Cathode and Anode Prepared with a Picosecond Pulsed Laser to Lithium Ion Battery (2) ~ Analysis of the Structure of Holed Cathode Layers ~. (25th June 2020) - Watanabe, Tatsuya; Gunji, Takao; Tsuda, Takashi; Ando, Fuma; Ando, Nobuo; Nakamura, Susumu; Hayashi, Narumi; Soma, Naohiko; Matsumoto, Futoshi
Abstract : A holed structure formed in cathodes with a picosecond laser method, which could remarkably improve the high-rate performance, was analyzed with scanning electron microscopy (SEM), Raman microprobe spectroscopy, focused ion beam (FIB)-SEM and mercury intrusion porosimetry. Percussion drilling by the laser beam was adapted to produce holes. During the formation of holes in the lithium iron phosphate (LiFePO4, LFP) cathode layer, a very small amount of LFP was transformed to Fe2 O3 by the laser irradiation. The laser evaporated the Al current collectors, and after laser ablation, Al deposits were formed on the sidewall of the holes by the cooling Al vapors. In addition, the laser irradiation caused an increase in the porosity of the LFP cathode layers due to the strong impact of the laser on the LFP layer. The three-dimensional (3D) electron pathway formed by the Al deposits and Al current collector plane and the increase in the porosity of the LFP layers enhanced Li + ion and electron transfer in the LFP cathode layer, resulting in a remarkable improvement of the high-rate performance of holed cathodes.